DhcSim — A Modelica library for simple modeling of complex DHC systems. (October 2021) - Bachmann, Max; Fürst, Yannick; Stanica, Diana; Kriegel, Martin
Abstract: District heating and cooling systems play an important role in future energy infrastructure by accessing local energy potentials, reducing temperature levels and exploiting synergies between energy systems. Therefore, a transition to next generation heating and cooling networks is needed, which can be realized by multi-level design, bidirectional usage of production and consumption or combined heating and cooling systems. This will increase the complexity of network design which may be hard to analyze and assess without the support of a system simulation. The following paper presents the dhcSim Modelica library which can be used to model complex district heating and cooling networks within a multi-level network structure. The library was developed as extension to the Modelica Buildings library and Modelica Standard library and provides a clear and easy to use model structure. This structure distinguishes between two-, four and multi-port-models which allows the modeling of highly complex multi-level DHC systems. The library provides models for both district heating and cooling and can be easily adapted to individual user cases. To illustrate the implementation of the library and how it can be used, a case study of a three-level district heating network is presented. Using the network simulation of the introduced example, it could be shown that the supply temperature requirements of some consumers could not be achieved by the proposed network and thus further action is needed.